Transformasi Sosial Melalui CSR Berbasis Pengelolaan Sampah: Evaluasi ekonomi, Sosial, dan Lingkungan Program Sipandu PT Cikarang Listrindo Tbk PLTU Babelan - Jauhari Eka Ronaldo; Dita Nurul Akbarani; Ihsan Sanjaya Akbar; Resha Delliani; Teodorus Iqbal (Khazanah Multidisiplin, 2025)
This study assesses community-level social transformation generated by SIPANDU, the CSR program of PT Cikarang Listrindo Tbk PLTU Babelan, across economic, social, and environmental dimensions. A descriptive qualitative design triangulates implementation documents, SROI reports (2022–2024), AAR, and the Community Satisfaction Index (IKM/CSI), using thematic analysis. Findings show SROI rising from 1.01 (2022) to 1.56 (2024) and IKM of 3.39/4 ≈ 84.75/100.  Economic effects include household income gains (Rp30–200k/month) and a strengthened community waste bank; environmental results cover ≥170 active customers and ≥3,729.65 kg of recyclables managed; social outcomes include higher participation (notably among women rangers) and tighter school–community networks. We conclude that a community-based CSR model can catalyze collective behavior change and circular-economy value creation; long-term success depends on institutional and financial autonomy beyond the corporate sponsor.